Is there any link between vitamin D and coronary no-reflow phenomenon? Vitamin D and Coronary No-reflow Phenomenon - Cerit, Levent; Kemal, Hatice; Cerit, Zeynep; Salem, Jane; Dokkmak, Anas; Etikan, Ilker; Duygu, Hamza (Progress in Nutrition, 2019)
Coronary no-reflow phenomenon (CNP) is associated with an increased risk of major cardiovascular adverse events. Vitamin D is closely associated with hypertension, stroke, myocardial infarction, cardiovascular adverse events, and endothelial dysfunction. Considering endothelial dysfunction is one of the main responsible factors of CNP. We aim to evaluate the association between vitamin D and CNP. The study group consisted of 109 patients. Taking into consideration the inclusion criteria, 60 patients with CNP and 49 patients without CNP were included in the study. CNP defined as TIMI grade <3 at the end of the procedure in the absence of any coronary dissection/spasm and/or less than 70% ST resolution at first hour ECG. Prevalence of CNP was found 55% in this study group. On univariate analysis age, balloon predilatation, stent diameter, serum creatinine, vitamin D, CRP level, initial TIMI flow <2, and reperfusion time >3 h were associated with CNP. On multivariate analysis reperfusion time >3 h, initial TIMI flow <2, and serum creatinine level were the independent predictors for CNP (OR 5.182; 95% CI: 3.159-8.327; p<0.001, OR 4.061; 95% CI: 2.729-6.327; p<0.001, OR 3.301; 95% CI: 1.937-4.623; p<0.001; respectively). In our study, we have found that reperfusion time >3 h, initial TIMI flow <2, and serum creatinine level were an independent predictor for CNP. Vitamin D was not found to be an independent predictor of CNP.